2019
DOI: 10.1002/jor.24236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osteochondral graft orientation in a biotribological test system

Abstract: Autologous osteochondral transplantation (AOT) utilizing autografts is a widely used technique for the treatment of small‐to‐medium cartilage defects occurring in knee and ankle joints. The application of viable cartilage and bone ensures proper integration, early weight bearing, as well as restoration of biomechanical and biotribological properties. However, alignment of the autografts onto the defect site remains a pivotal aspect of reinstating the properties of the joint toward successful autograft integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The osteochondral plugs (8‐mm diameter, 15‐mm length) were harvested from the medial femoral condyle using a cutting tube (OATS; Arthrex Inc., Naples, FL) within 24 h after sacrifice. The anteroposterior orientation was marked to arrange the osteochondral cylinder, as previously described . Each knee yielded nine samples, which were washed with phosphate‐buffered saline (PBS) (Sigma‐Aldrich Chemie GmbH, Steinheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The osteochondral plugs (8‐mm diameter, 15‐mm length) were harvested from the medial femoral condyle using a cutting tube (OATS; Arthrex Inc., Naples, FL) within 24 h after sacrifice. The anteroposterior orientation was marked to arrange the osteochondral cylinder, as previously described . Each knee yielded nine samples, which were washed with phosphate‐buffered saline (PBS) (Sigma‐Aldrich Chemie GmbH, Steinheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic activity of chondrocytes within the cartilage of the osteochondral plugs was measured using an XTT assay kit (Cell Proliferation Kit II (XTT); Roche Diagnostics, Basel, Switzerland), as previously described . In short, cartilage was cut from the osteochondral grafts and bisected longitudinally, with equal distribution of the contact area on both pieces of articular cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in our previous study, 23 the use of a cartilage-on-cartilage test system reflects native physiological conditions more accurately than testing against a metal or glass counterpart. This test setup is particularly advantageous when imitating inflammatory reactions, as this approach not only depends on the test fluid but also on how the cartilage matrix of both osteochondral grafts changes during treatment.…”
Section: Discussionmentioning
confidence: 78%
“…A test system with a specially designed sample holder, which was already applied in previous studies, 23 , 24 was used and is shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The process ensures sterile conditions for tests on biological samples that are highly sensitive to the environmental conditions. As the setup is designed for consecutive projects (Bauer et al, 2019) that require possible analysis techniques, such as mass spectroscopy, cell counting with a hemocytometer or microarray methods, it is crucial to inhibit interaction with common ambient conditions that may generate artefacts.…”
Section: Setup Of the Tribotestmentioning
confidence: 99%